2019 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--33078
|View full text |Cite
|
Sign up to set email alerts
|

Making Space for the Women: Exploring Female Engineering Student Narratives of Engagement in Makerspaces

Abstract: is a Ph.D. student in Counseling Psychology at Arizona State University. She has previously earned her B.S. in Psychology and M.A. in Counseling Psychology. Her previous research has examined Asian American ethnic identity formation, racial/ethnic and gender differences in perceptions of financial stress, and the integration of a three apprenticeships framework in engineering. Her current research emphasizes a health belief approach to examine the likelihood of mental health help-seeking behaviors among Asian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Perhaps further limiting engagement, is the social construction of making and makerspaces as masculine (Meyer 2018), or perhaps even more so, the discipline of engineering itself (Hatmaker 2013;McIlwee and Robinson 1992). Even with these cultural barriers, through, women do engage; however, women choosing to engage in making likely face gender bias and unfair expectations about their abilities (Lam et al (2019), as well as benevolent and hostile sexism (Tomko et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps further limiting engagement, is the social construction of making and makerspaces as masculine (Meyer 2018), or perhaps even more so, the discipline of engineering itself (Hatmaker 2013;McIlwee and Robinson 1992). Even with these cultural barriers, through, women do engage; however, women choosing to engage in making likely face gender bias and unfair expectations about their abilities (Lam et al (2019), as well as benevolent and hostile sexism (Tomko et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Our hope is that this work can help managers and directors of makerspaces in higher education create more inclusive makerspaces. In our work, we have found that engaging in makerspaces promotes agency and engineering identity for Black male undergraduates [10] and increased confidence and opportunities to learn for female undergraduate students [11]. In addition, we found that the recommendations that students make for improving makerspaces differ as women and men who belong to underrepresented groups tend to suggest more social changes and majority men request more equipment [12].…”
Section: Discussionmentioning
confidence: 79%
“…This heteronormative culture resulted in Black men not realizing their agency and development of their engineering identity as well as other Black men who engaged in the makerspaces at a Minority Serving Institution (MSI). Lam, Cruz, Kellam, and Coley found that female students perceived gender bias within the makerspaces that, in some cases, resulted in an intimidating, hostile, and non-inclusive environment [11]. Even in spite of these negative findings, some female students also experienced increased confidence and learning opportunities when engaging in makerspaces.…”
Section: Literature Reviewmentioning
confidence: 99%